2013
DOI: 10.1002/jbm.a.34759
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable weft‐knitted intestinal stents: Fabrication and physical changes investigation in vitro degradation

Abstract: Biodegradable stents can alleviate intestinal obstruction and stenosis in patients. The objective of this study was to develop a biodegradable polydioxanone (PDO) stent using weft-knitting technology and then investigate its biodegradation behaviors in vitro. PDO monofilament with linear density of 100 ± 10 tex was knitted into a tubular stent using a tubular weft-knitting machine. The physical and mechanical properties were evaluated according to the British standard BS EN 13895:2003 and ISO 7198:1998. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 25 publications
7
27
0
Order By: Relevance
“…This allowed us to separately study the effect of stent material viscoelasticity on the radial force and pressure. Moreover, previous investigations of the in vitro chemical degradation of polydioxanone [12,18] show that the Young's modulus of polydioxanone and radial force and pressure of the unloaded polydioxanone stent are maintained for up to 6-8 weeks. These findings prove that the force relaxation observed within the first 48 h is caused by viscoelasticity and not the chemical degradation of polydioxanone.…”
Section: Plos Onementioning
confidence: 93%
See 1 more Smart Citation
“…This allowed us to separately study the effect of stent material viscoelasticity on the radial force and pressure. Moreover, previous investigations of the in vitro chemical degradation of polydioxanone [12,18] show that the Young's modulus of polydioxanone and radial force and pressure of the unloaded polydioxanone stent are maintained for up to 6-8 weeks. These findings prove that the force relaxation observed within the first 48 h is caused by viscoelasticity and not the chemical degradation of polydioxanone.…”
Section: Plos Onementioning
confidence: 93%
“…Many studies have investigated stent material properties. These studies have mainly focused on biocompatibility [14], corrosion resistance [12,13,[15][16][17], "simple elastic" stress-strain characteristics [13,18,19], and elastic memory [16,[20][21][22]. Other studies have investigated or developed new materials [23][24][25] and stent designs [13,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable, absorbable stents are preferred in some instances to avoid these complications . The use of polydioxanone biodegradable stents has been reported in experimental and clinical studies . Novotny et al used a rabbit airway model and reported polydioxanone stents were completely absorbed 10 weeks after implantation, and only mild lymphoplasmacytic inflammation and minimal residual scar tissue remained at 15 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53] The use of polydioxanone biodegradable stents has been reported in experimental and clinical studies. [54][55][56][57] Novotny et al 55 used a rabbit airway model and reported polydioxanone stents were completely absorbed 10 weeks after implantation, and only mild lymphoplasmacytic inflammation and minimal residual scar tissue remained at 15 weeks. In our stallion, the stent was not evident on ultrasound examination 155 days after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, biodegradable and or drug-loaded stents have been demonstrated as an option to treat intestinal obstructions and stenosis [184, 185] . The major advantages of biodegradable stents are that they avoid long-term complications and do not require removal, thus avoiding further surgeries and potential morbidity [186, 187] .…”
Section: Applications Of Silk-based Biomaterials For Biomedical Tementioning
confidence: 99%